Global Conflicts and the Macro-regional Modernities. Interview with Marek Hrubec - Marek Hrubec (Communication Today, 2025)
The interview focuses on Marek Hrubec’s Critical theory of global society and politics. It presents a critique and explanation of social, economic, political, media, cultural issues, and explains normative alternatives. It deals with the crisis of global capitalism and the contemporary situation in the West. It compares it with the recent developments in alternative modernities in the Islamic countries, China and Russia, India and South America, and Africa. It addresses issues of global conflicts and injustice, global poverty, intercultural dialogue, corporate power, revolution and transformation, the United Nations and the requirements of cosmopolitan arrangement, and the personal experience from Central Europe and Sub-Saharan Africa.